Inflammation induced preterm labor and birth. (September 2018) - Gilman-Sachs, Alice; Dambaeva, Svetlana; Salazar Garcia, Maria D.; Hussein, Youssef; Kwak-Kim, Joanne; Beaman, Kenneth
Highlights: Preterm birth and labor occurs due to many risk factors. Infection and/inflammation is a major risk factor. Long term use of antibiotics is not preventative. Animal models for LPS induced inflammation are available. New biomarkers and treatments are needed. Abstract: Preterm birth which occurs before 37 weeks gestation is one of the most common obstetrical complication in humans. After many studies, it appears that "not one answer fits all" regarding the risk factors, causes and the treatments for this syndrome. However, it is becoming more evident that one of the major risk factors is inflammation and/or infection in the fetoplacental unit. In animal models (usually consisting of mice injected with lipopolysaccharide at 14 days of gestation), IL-22 and IL-6 have been identified as factors related to preterm birth. There are some clinical tests available to determine the risk for preterm labor and delivery, which can be identified before, during early, or at mid-gestation. However, treatment of preterm birth with antibiotics so far has not been "curable" and studies using anti-inflammatory treatments are not readily available. More studies regarding causes and treatments for preterm labor and delivery in humans are necessary to prevent neonatal deaths and/or developmental abnormalities associated with this common syndrome.